Strategi Petani Padi dalam Menghadapi Gagal Panen di Desa Jaya Makmur Kecamatan Katingan Kuala Kabupaten Katingan: Strategy of Rice Farmers in Facing Harvest Failure in Jaya Makmur Village Katingan Kuala District, Katingan District - Karyadi, Karyadi; Putra, Surya Ade (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2015)
This research is about the strategy of rice farmers in facing crop failure, which depends on agrarian sources for agriculture to be carried out using qualitative research methods. Selection of these methods with consideration, qualitative methods have advantages, namely because qualitative methods see the processes that occur in the field rather than the products of the object of research. As an effort of farmers to maintain their subsistence in this study using inductive data analysis. To examine the background of phenomena that cannot be investigated using quantitative research, to examine something in depth and background for example about motivation, roles, attitudes and perceptions used by researchers who want to be seen in terms of the process. Based on the results of the study, the research strategies carried out by rice farmers in Jaya Makmur Village are 1. Subsistence alternative strategies, namely to make other alternatives to obtain additional income in fulfilling living needs such as gardening, fishing, carpenters, sewing crafts, laborers and others other, 2. The strategy of tying the belt tighter is the concept of tying the belt tighter has the understanding of saving on basic needs and more regulating their expenses with the income they earn, 3. Network/relationship strategy that is social network is a concept by interacting with people others and are closely related and harmonious with other people such as neighbors, work relatives, and family.